Physicochemical, technological, and sensory characteristics of fresh multigrain pasta: A multicomponent mixture experiments approach - de Oliveira Filho, Josemar Gonçalves [UNESP]; dos Santos, Daiane Costa; Silva, Morhana Santos; do Prado Carvalho, Thalyta; Lemes, Ailton Cesar; Egea, Mariana Buranelo (Hindawi, 2021)
Pasta is a popular food throughout the world and its quality can be measured mainly by its appearance, taste, and texture. The aim of this work was first to produce fresh multigrain pasta with a maximization of the sensorial properties and then evaluate the effects of the unconventional flours (rice, oat, and soy) on the physicochemical properties and sensory profile. Soy flour alone contributed to most modifications, such as an increase in yellow color (8.9–13.5, b* parameter), a decrease in the homogeneous appearance, texture (4.4–1.7 N), and cooking time (13 to 8.3 min). However, the mixture of the three flours contributed to increasing the sensorial hardness (2.1–4.1), making it more al dente as expected for fresh pasta. Fresh pasta with a mixture of rice, oat, and soy flour improves the nutritional value of the pasta in relation to control, increasing the protein (17.8 to 32.6 g/100 g) and ash (2.5 to 2.9 g/100 g) contents, and reducing the content of carbohydrates (77.6 to 62.4 g/100 g). In addition, the lipid (1.95 and 2.0 g/100 g), and caloric values (399.6 and 398.3 kcal) remained the same for fresh control and enriched pasta, respectively. Novelty impact statement: The incorporation of unconventional flours can be used as a vehicle to provide important nutritional components; Soy flour contributed with the yellow color of fresh multigrain pasta; Fresh multigrain pasta can be more al dente as expected for fresh pasta.